Delays in Initiation of Disease-Modifying Therapy in Rheumatoid Arthritis Patients: Data from a US-Based Registry. Issue 2 (December 2015) - Pappas, Dimitrios; Kent, Jeffrey; Greenberg, Jeffrey; Mason, Marc; Kremer, Joel; Holt, Robert
Abstract Introduction The goal of this study was to evaluate how frequently rheumatoid arthritis (RA) therapy is instituted promptly and to describe the characteristics of patients who are not treated early upon diagnosis. Methods The percentage of patients who at the time of enrollment in the Corrona registry were not receiving any RA-directed therapy was evaluated and their characteristics were summarized. The time to subsequent initiation of any RA-directed therapy was also estimated. Results Among 35, 485 patients enrolled in Corrona, 34, 735 (97.9%) were on appropriate therapy for RA and 750 (2.1%) had no history of any RA-directed therapy at time of enrollment. Among patients without any history of RA-directed therapy, the overall disease duration was 5.5 ± 9.0 years, with only 50.7% of patients having early disease (duration ≤1 year). Patients with no history of directed RA therapy did not have lower disease activity at enrollment compared with those receiving therapy. Clinical Disease Activity Index (CDAI) was 18.3 ± 15.0; 34% of patients had high and 27.6% moderate disease activity by CDAI. Patients were followed for a median (95% CI) time of 29.5 months (24.6–33.8). During the follow-up period, 372 out of 750 (49.6%) patients initiated RA-directed therapy. The median time to initiation of any RA-directed therapy was 12.1 months (95% CI 9.3–14.8). Conclusion In this registry analysis, approximately 98% of patients were on appropriate RA therapy for their RA. However, a minority of patients with RA did not have a history of receiving disease-modifying therapy within a mean of approximately 5 years of RA onset and approximately 50% of them did not initiate any therapy within 12 months of registry follow-up. This delay in therapy did not appear to be related to a better controlled, or lower, RA disease activity state at the time of enrollment in the registry. Funding Corrona, LLC.